Chronic Inhibition of Mitochondrial Dihydrolipoamide Dehydrogenase (DLDH) as an Approach to Managing Diabetic Oxidative Stress - Xiaojuan Yang; Jing Song; Liang-Jun Yan (MDPI AG, 2019)
Mitochondrial dihydrolipoamide dehydrogenase (DLDH) is a redox enzyme involved in decarboxylation of pyruvate to form acetyl-CoA during the cascade of glucose metabolism and mitochondrial adenine triphosphate (ATP) production. Depending on physiological or pathophysiological conditions, DLDH can either enhance or attenuate the production of reactive oxygen species (ROS) and reactive nitrogen species. Recent research in our laboratory has demonstrated that inhibition of DLDH induced antioxidative responses and could serve as a protective approach against oxidative stress in stroke injury. In this perspective article, we postulated that chronic inhibition of DLDH could also attenuate oxidative stress in type 2 diabetes. We discussed DLDH-involving mitochondrial metabolic pathways and metabolic intermediates that could accumulate upon DLDH inhibition and their corresponding roles in abrogating oxidative stress in diabetes. We also discussed a couple of DLDH inhibitors that could be tested in animal models of type 2 diabetes. It is our belief that DLDH inhibition could be a novel approach to fighting type 2 diabetes.